Acrylamide Decreases Cell Viability, and Provides Oxidative Stress, DNA Damage, and Apoptosis in Human Colon Adenocarcinoma Cell Line Caco-2 - Adriana Nowak; Małgorzata Zakłos-Szyda; Dorota Żyżelewicz; Agnieszka Koszucka; Ilona Motyl (Molecules, 2020)
Acrylamide (AA) toxicity remains an interesting subject in toxicological research. The aim of the research performed in this paper was to determine mechanisms of cyto- and genotoxic effects of AA on the human colon adenocarcinoma cell line Caco-2, to estimate the inhibitory concentration (IC)50 values in cell viability assays, to measure the basal and oxidative DNA damage as well as the oxidative stress leading to apoptosis, and to assess the morphological changes in cells using microscopic methods. It has been proven that AA induces cytotoxic and genotoxic effects on Caco-2 cells. Higher cytotoxic activity was gained in the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay compared with the PrestoBlue assay, with IC50 values of 5.9 and 8.9 mM after 24 h exposure, respectively. In the single-cell gel electrophoresis assay, the greatest DNA damage was caused by the highest concentration of acrylamide equal to 12.5 mM (89.1% ± 0.9%). AA also induced oxidative DNA damage and generated reactive oxygen species (ROS), which was concentration dependent and correlated with the depletion of mitochondrial membrane potential and apoptosis induction. In the microscopic staining of cells, AA in the dosage close to the IC50 induced morphological changes typical for apoptosis. Taken together, these results demonstrate that AA has a pro-oxidative effect on Caco-2 cells, leading to apoptotic cell death.